OPTIMALISASI PEMANFAATAN PEKARANGAN RUMAHDALAM MENANAM TOGA (TANAMAN OBAT KELUARGA) BAGI MASYARAKAT DI DESA TRITIRO KEC. BONTOTIRO KAB. BULUKUMBA - GH, Muliana; Pratiwi, Andi Citra; Muis, Abd; Azis, Andi Asmawati; Patongai, Dian Dwi Ulan Sari; Sahribulan, Sahribulan (Universitas Negeri Makassar, 2023)
Community service partners are housewives who live in Tritiro Village, Samboang District, Bulukumba Regency. The majority of people's income comes from fishing and the amount is uncertain every month. The location of this service is around a cliff that borders the coast. Yards of residents' houses are generally not used optimally, only left empty and overgrown with wild plants, or some ornamental plants. The solution provided is training in planting family medicinal plants that can be used for consumption of family herbal medicines. If production can exceed needs, produce or plants can be sold to supplement family income. The method is carried out by providing (1) Introduction to family medicinal plants, (2) Counseling on optimizing the use of the home yard in growing family medicinal plants, (3) Introduction to fertile and infertile soil (planting medium), (4) TOGA planting training (family medicinal plants). Keywords: Medicinal plants, Optimizing the home yard.